Considerations about Adapting to IFRS S1 and S2 With Regard to Sustainability Reporting: Research Regarding Enterprises on the BIST Sustainability 25 Index - Gözde Nezriye Bi̇rcan; İrem Özcan (Muhasebe Enstitüsü Dergisi)
According to International Financial Reporting Standards (IFRS), the financial information enterprises report must be comparable, verifiable, understandable, and presented timely, as well as relevant and faithfully represented. In today’s world and the prominence of sensitivities toward environmental, social, and managerial issues such as pandemics, climate crises, and waste problems, as well as the increasing impact these issues have on the decision-making process of financial statement users, reporting sustainability-related information that includes this financial information with the characteristics stated above has been released as a required need. The study examines the degree to which financial reports and other related reports from enterprises on the BIST Sustainability 25 Index comply with the requirements of the exposure drafts of the IFRS S1 and IFRS S2 based on these requirements using descriptive and content analyses to explain the important points and deficiencies identified in the process of reporting sustainability-related information.